The Effect of Jump Rope Training Program on Increase Dynamic Balance in Deaf Children SLB-B Yayasan Pendidikan Tunas Bangsa (YPTB) Malang City - Putri, Salva Almayda; Raharjo, Slamet; Andiana, Olivia (Sports Medicine Curiosity Journal, 2023)
A deaf person is a person who has partial or total hearing disorders or imperfections caused by the failure of the hearing sense to function properly, so that it can affect their life. Most deaf children experience vestibular deficits which cause decreased balance function and discomfort in life. The development of visual, perceptual, and motor skills as well as sensory integration can all be impacted by balance issues. The purpose of this study is to look into the effects of missing training sessions both before and after therapy. This study used a one-group pretest-posttest research design and a quantitative, pre-experimental methodology. The population studied was 38 deaf children, and 30 deaf children were selected as research samples using a purposive sampling technique. This research shows the results that the skipping training program has a positive effect by increasing dynamic balance in deaf children from Yayasan Tunas Bangsa (YPTB) Malang City. The results of this research show a 0.000 significant level was obtained from the paired samples t-test statistical test findings. The conclusion is that the skipping program has an impact on improving dynamic balance in deaf children from the Yayasan Tunas Bangsa, as seen from the increase in scores on the post-test.